Pengembangan Bahan Ajar E-Modul Pada Pelajaran Ilmu Pengetahuan Sosial (IPS) Di Sekolah Menengah Pertama (SMP) - Eka Fitriani; Rambang Muharramsyah; Muhammad Iqbal (LPPM Institut Pendidikan Nusantara Global, 2026)
This study was motivated by the limited use of digital teaching materials in social studies learning at SMP Negeri 2 Sawang, while students need learning resources that are visual, contextual, and accessible. This research aimed to develop an interactive e-module entitled